Clinical features and prognostic factors of cardiorenal anemia syndrome in China: a retrospective single-center study - Mengyue Zhu; Min Liu; Chunlei Lu; Dafeng He; Jiao Li; Xia Xu; Ying Cui; Chuanyan Zhao; Jun Xu; Gang Zhou; Hongbin Mou; Guangyu Bi; et al. (BMC Cardiovascular Disorders)
Abstract Background There is little research on cardiorenal anemia syndrome (CRAS) in China. This study was to describe the characteristics of patients with CRAS and to explore risk factors of all-cause death. Methods A total of 81,795 patients were hospitalized from August 2012 to August 2021 in the nephrology department and cardiology department, of which 820 patients with CRAS were recruited into this study. The 820 patients were divided into three groups based on New York Heart Association (NYHA) functional class: a NYHA Class II group (n = 124), a NYHA Class III group (n = 492), and a NYHA Class IV group (n = 204). Demographics and laboratory tests were collected and risk factors of all-cause death were analyzed. The primary endpoint of the study was all-cause death. Results 820 patients were included, with a median age of 65.00 (51.00–75.00) years and 61.2% were men. The median follow-up was 27.0 (13.0–51.0) months. 416 (50.7%) patients died during follow-up. Age, smoking history, cerebral infarction, NYHA functional class, albumin, serum creatinine (SCr), left ventricular end-diastolic diameter (LVEDD), and left ventricular ejection fraction (LVEF) remained independent predictors of all-cause mortality risk in patients with CRAS (P < 0.05) after adjusting to the potential confounders. Conclusions In patients with CRAS, older age, smoking history, and more advanced systolic heart failure and renal failure correlated with worse clinical outcomes at follow-up.